Asymptomatic versus Symptomatic Patients with Severe Aortic Stenosis - Norio Kanamori; Tomohiko Taniguchi; Takeshi Morimoto; Hiroki Shiomi; Kenji Ando; Koichiro Murata; Takeshi Kitai; Yuichi Kawase; Chisato Izumi; Makoto Miyake; Hirokazu Mitsuoka; Masashi Kato; et al. (Scientific Reports, 2018)
Abstract It is unknown how much different are the clinical outcomes between asymptomatic and symptomatic patients with severe aortic stenosis (AS). In the CURRENT AS registry enrolling 3,815 consecutive patients with severe AS, we compared the long-term outcomes between 1808 asymptomatic and 1215 symptomatic patients (exertional dyspnea: N = 813, syncope: N = 136, and angina: N = 266) without heart failure (HF) hospitalization. Symptomatic patients had greater AS severity, and more depressed left ventricular function than asymptomatic patients without much difference in other baseline characteristics. During a median follow-up of 3.2 years, aortic valve replacement (AVR) was performed in 62% of symptomatic patients, and 38% of asymptomatic patients. The cumulative 5-year incidences for the primary outcome measure (a composite of aortic valve-related death or HF hospitalization) was higher in symptomatic patients than in asymptomatic patients (32.3% versus 27.6%, P < 0.001). After adjusting for AVR and other variables, the greater risk of symptomatic relative to asymptomatic patients for the primary outcome measure was significant (hazard ratio 1.64, 95% confidence interval 1.41–1.96, P < 0.001). In conclusions, the excess risk of symptomatic relative to asymptomatic patients with severe AS for the aortic valve-related event was significant. However, the prevalence of AVR in symptomatic patients was not optimal.